The Role of Gender Equality in Economic Development: A Cross-Cultural Analysis - Aziza Sharipova; Dilorom Akhmedova (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
This research examines the role of gender equality in fostering economic development across different cultural contexts. By analyzing data from various countries, the study evaluates how gender equity in education, employment, and political participation correlates with economic growth. Findings suggest that countries with greater gender equality experience more sustainable economic development, underscoring the importance of inclusive policies.